Functionalized Nanomaterials (IntechOpen, 2023)
Generally the nanometer scale covers from 1 to 100 nm while discussing the nanomaterials. Nanomaterials have very high potency and emerge with large applications piercing through all the discipline of knowledge, leading to industrial and technological growth. Nanotechnology is a multidisciplinary science that has its roots in fields such as colloidal science, device physics, and biomedical and supramolecular chemistry. The main objective of the book is to cover maximum areas focusing on synthesis, characterization with various microscopic techniques, and multiple applications. This book is divided into two sections with Non-carbon Compounds and Carbon Compounds. The synthesis, characterization, and applications of metal, metal oxides, and metal hydroxide nanoparticles are covered in the section Non-carbon Compounds, while the section Carbon Compounds focuses on the carbon nanotubes, graphite oxide, graphene oxide, etc.